Heterogeneous catalytic CO2 conversion to value-added hydrocarbons - Dorner, Robert W; Hardy, Dennis R; Williams, Frederick W; Willauer, Heather D (Energy & environmental science, 2010)
The impact that anthropogenic CO 2 is having on the environment has been thoroughly documented over the last 20 years. Many different technologies have been proposed to reduce its impact on global warming such as geological sequestration. However, an interesting and attractive alternative would be the recycling of the gas into energy-rich molecules. Iron rather than cobalt catalysts, based on the Fischer-Tropsch technology, have shown the greatest promise in converting CO 2 to value-added hydrocarbons. The addition of co-catalysts is, however, essential to fine tune the product distribution to the more desired alkene products. The role that both the promoter and support play on the catalyst's activity is reviewed. This review examines work done in the field of catalytic CO 2 conversion to value-added hydrocarbons over Fischer-Tropsch based catalysts.